ABI4 and its role in chloroplast retrograde communication - León, Patricia; Gregorio, Josefat; Cordoba, Elizabeth (Frontiers in Plant Science, 2013)
The acquisition of plastids is a landmark event in plant evolution. The proper functionality of these organelles depends on strict and continuous communication between the plastids and the nucleus to precisely adjust gene expression in response to the organelle’s requirements. Signals originating from the plastids impact the expression of a variety of nuclear genes, and this retrograde communication is essential to couple the nuclear expression of plastid-localized products with organelle gene expression and, ultimately, functionality. Major advances have been made in this field over the past few years with the characterization of independent retrograde signaling pathways and the identification of some of their components. One such factor is the nuclear transcriptional factor ABI4 (ABA-INSENTIVE 4). ABI4, together with the plastid PPR GUN1 protein, has been proposed to function as a node of convergence for multiple plastid retrograde signaling pathways. ABI4 is conserved among plants and also plays important roles in various critical developmental and metabolic processes. ABI4 is a versatile regulator that positively and negatively modulates the expression of many genes, including other transcriptional factors. However, its mode of action during plastid retrograde signaling is not fully understood. In this review, we describe the current evidence that supports the participation of ABI4 in different retrograde communication pathways. ABI4 is regulated at the transcriptional and post-transcriptional level. A known regulator of ABI4 includes the PTM transcription factor, which moves from the chloroplast to the nucleus. This transcription factor is a candidate for the transmission of retrograde signals between the plastid and ABI4.